2017
DOI: 10.1103/physrevb.96.144104
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction study of the inverse spinels Co2TiO4 and Co2SnO4

Abstract: We report a detailed single-crystal and powder neutron diffraction study of Co2TiO4 and Co2SnO4 between the temperatures 1.6 K and 80 K to probe their spin structures in the ground state. For both compounds the strongest magnetic intensity was observed for the (111)M reflection due to ferrimagnetic ordering, which sets in below TN = 48.6 K and 41 K for Co2TiO4 and Co2SnO4, respectively. An additional low intensity magnetic reflection (200)M was noticed in Co2TiO4 due to the presence of an additional weak antif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 82 publications
8
33
0
Order By: Relevance
“…Figure 4(a) presents the Co2p spectra of T 1 and T 2 , respectively, indicating that there are doublet peaks of Co 2p 3/2 and Co 2p 1/2 located at 780.46 and 795.96 eV for T 1 and 780.62 and 796 eV for T 2 , respectively. The energy splitting (ΔE) values of the divalent and trivalent Co ions are 15.4 and 15.1 eV for T 1 and T 2 , respectively, which are consistent with values reported in the literature 19 . The Co2p spectra of T 1 and T 2 are fitted into six peaks with binding energies of approximately 780.4 and 795.8 eV for Co 2+ and 782.2 and 797.3 eV for Co 3 + 5,19 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Figure 4(a) presents the Co2p spectra of T 1 and T 2 , respectively, indicating that there are doublet peaks of Co 2p 3/2 and Co 2p 1/2 located at 780.46 and 795.96 eV for T 1 and 780.62 and 796 eV for T 2 , respectively. The energy splitting (ΔE) values of the divalent and trivalent Co ions are 15.4 and 15.1 eV for T 1 and T 2 , respectively, which are consistent with values reported in the literature 19 . The Co2p spectra of T 1 and T 2 are fitted into six peaks with binding energies of approximately 780.4 and 795.8 eV for Co 2+ and 782.2 and 797.3 eV for Co 3 + 5,19 .…”
Section: Resultssupporting
confidence: 90%
“…The energy splitting (ΔE) values of the divalent and trivalent Co ions are 15.4 and 15.1 eV for T 1 and T 2 , respectively, which are consistent with values reported in the literature 19 . The Co2p spectra of T 1 and T 2 are fitted into six peaks with binding energies of approximately 780.4 and 795.8 eV for Co 2+ and 782.2 and 797.3 eV for Co 3 + 5,19 . Furthermore, two satellite peaks are observed at 786.13 and 802.6 eV for T 1 and 785.84 and 802.45 eV for T 2 , respectively 19 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…From the occupations observed, it was concluded that the cationic distribution for the CTO in CTO/RGO is (Co 0.98 Ti 0.02 ) Td (Co 0.96 Ti 1.04 ) Oh O 4 and in CTO+RGO is (Co 0.96 Ti 0.04 ) Td (Co 0.98 Ti 1.02 ) Oh O 4. These results indicate that the tetrahedral sites are not fully occupied by Co 2+ ions since there is a small amount of Ti 4+ , unlike the work reported by S. Thota et al, where CTO was synthesized by a solid-state reaction, with Co 2+ and Co 3+ in both crystallographic sites and Ti 3+ in the octahedral site [48,60]. These differences in the distribution of the cations in the crystallographic sites can be attributed to the method of synthesis and the precursors used, suggesting that the lower reaction temperature possibly means there is insufficient energy to permit full ordering or mixing of the cations, and thus some inhomogeneity persists.…”
Section: Resultsmentioning
confidence: 74%
“…Additionally, magnetic interaction mechanisms in Co 2 VO 4 have been proposed using semi-empirical rules for magnetic interactions in spinels [18,20]. While temperature-driven magnetization reversal for Co 2 VO 4 , Co 2 TiO 4 , and Sr 2 DyRuO 6 has been experimentally explored [18,[21][22][23][24], the fundamental driving mechanism behind MR in the inverse spinels remains to be understood.…”
Section: Introductionmentioning
confidence: 99%